(3QSGdI aj UjGe jhe GdTcs - (3GdebOSj GdLeGYjdj, GdUGdMj, GdOeTbj, GdTGaYj, CHh YHO Gddg, GHf bOGeI, TeS GdOjf, eMeO Hf CMeO Hf YHO GdgGOj, J (B744 (3g`s ((3CMeO Hf jhSa Hf LGHQ Hf YHO Gddgs)
(3ChdgG (B:s
(3aUd aj GdcdGe Ydi eSCdI GdZje , eNJUQ Ch HjGf GdGNJdGa ajgG de jKHJ Yf GdfHj Udi Gddg Ydjg hSde hdG Yf CMO ef GdUMGHI QVhGf Gddg Ydjge EjLGH GdUhe jhe GdKdGKjf ef TYHGfs
(3BNQgG (B:s
(3abO YQa Cf eG fbd aj gPG Yf GdUMGHI dG jOd Ydi GdhLhH hdh KHJ GdhLhH YfO HYVge de jcf MLI eY eNGdaI ZjQg heY eNGdaI GdCMGOjK GdUMjMI GdUQjMI hGddg SHMGfg hJYGdi CYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 326s
(3eYLe GdeDdajf (B3 / 78s
(3TPQGJ GdPgH (B6 / 141s
(3GdHOQ GdWGdY (B2 / 108s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs